Modern Hyper- and High Inflations - Fischer, Stanley (IMF Working Papers; Working Paper ;, 2002)
Since 1947, hyperinflations (by Cagan's definition) in market economies have been rare. Much more common have been longer inflationary processes with inflation rates above 100 percent per annum. Based on a sample of 133 countries, and using the 100 percent threshold as the basis for a definition of very high inflation episodes, this paper examines the main characteristics of such inflations. Among other things, we find that (i) close to 20 percent of countries have experienced inflation above 100 percent per annum; (ii) higher inflation tends to be more unstable; (iii) in high-inflation countries, the relationship between the fiscal balance and seigniorage is strong both in the short and longrun's; (iv) inflation inertia decreases as average inflation rises; (v) high-inflation is associated with poor macroeconomic performance; and (vi) stabilizations from high inflation that rely on the exchange rate as the nominal anchor are expansionary.